2004
DOI: 10.1124/dmd.32.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Pharmacokinetics of Fluoxetine and Norfluoxetine Enantiomers in Pregnant Sheep

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:We examined the stereoselective disposition of fluoxetine (FX) and its metabolite norfluoxetine (NFX) in five pregnant sheep. Racemic FX was administered i.v. to the ewe (50 mg) and the fetus (10 mg) on separate occasions. Maternal and fetal blood, maternal urine, and fetal amniotic and tracheal fluid samples were collected for 72 h. FX and NFX isomers were quantified by gas chromatographymass spectrometry. They rapidly crossed the place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…At 0700 h on infusion d 1, a 10-mL bolus injection of either 70 mg FX or sterile water was given over 2 min into the maternal femoral vein catheter followed by continuous infusion of 98.5 g/kg/d FX or an equivalent volume of sterile water for 8 d. The loading dose and infusion rate were calculated based on volume of distribution and systemic clearance data obtained from FX i.v. bolus pharmacokinetic studies in pregnant sheep previously performed in our laboratory (25). At 0700 h each day, maternal and fetal blood samples were collected for analysis of blood gases (1 mL) and plasma concentration of FX, cortisol, and ACTH (1.5 mL) and stored at Ϫ20°C for 2 wk and then at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 0700 h on infusion d 1, a 10-mL bolus injection of either 70 mg FX or sterile water was given over 2 min into the maternal femoral vein catheter followed by continuous infusion of 98.5 g/kg/d FX or an equivalent volume of sterile water for 8 d. The loading dose and infusion rate were calculated based on volume of distribution and systemic clearance data obtained from FX i.v. bolus pharmacokinetic studies in pregnant sheep previously performed in our laboratory (25). At 0700 h each day, maternal and fetal blood samples were collected for analysis of blood gases (1 mL) and plasma concentration of FX, cortisol, and ACTH (1.5 mL) and stored at Ϫ20°C for 2 wk and then at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…A rapid, sensitive, and selective chiral assay for FX and NFX enantiomers using gas chromatography mass spectrometry with selective ion monitoring developed in our laboratory was used for plasma FX analysis as previously described (25). Samples were analyzed for plasma FX and NFX concentrations only if maternal and fetal blood samples were collected at all time points in the protocols from 0700 h on the preinfusion day to 72 h postinfusion (n ϭ 6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same experiments showed that radioactivity (i.e., FLU and/or its metabolites) crosses the placenta about 4 hours after drug administration, and accumulates in the brain and the thymus [81]. In pregnant sheep, FLU rapidly crosses the placenta after maternal administration; the foetus shows no demethylation nor glucuronidation activity and in both ewe and foetus FLU is extensively bound to plasma proteins [82]. Studies on isolated perfused human placenta (obtained immediately after delivery) have been carried out.…”
Section: Pharmacokinetics During Pregnancy and Lactationmentioning
confidence: 74%
“…A thorough nonclinical study to evaluate the placental transfer of fl uoxetine in sheep was performed by Kim et al (2004) . Using catheterized sheep, it was possible to administer fl uoxetine to either the ewe or the fetus and collect multiple maternal and fetal blood samples.…”
Section: Sample Datamentioning
confidence: 99%